HERC6 is upregulated in peripheral blood mononuclear cells of patients with systemic lupus erythematosus and promotes the disease progression. (17th November 2022) - Cao, Ling; Zhang, Hui; Bai, Jin; Wu, Tingting; Wang, Yingjuan; Wang, Ning; Huang, Caihong
Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease. Peripheral blood mononuclear cells (PBMCs) are any peripheral blood cell with round nuclei, including lymphocytes (T cells, B cells) and monocytes, whose physicochemical properties are randomized by obvious immune changes, and are a potentially effective source of SLE blood test samples and therapeutic targets. This study aimed to explore the upregulation molecules of PBMCs in patients with SLE and to explore their biological role. Homologous to the E6-AP carboxyl terminus (HECT) and regulator of chromosome condensation 1 (RCC1)-like domain (RLD) containing E3 ubiquitin protein ligase family member 6 (HERC6) expression was found significantly upregulated in four Gene Expression Omnibus gene sets. Moreover, HERC6 expression was upregulated in PBMCs from SLE patients compared with that in PBMCs from normal donors. HERC6 was significantly associated with SLE clinical phenotypes such as complement C3 content, erythrocyte sedimentation rate, and SLE disease activity index. In vitro, knockdown of HERC6 inhibited PBMC apoptosis, inflammatory response, and janus kinase (JAK)/signal transducer and activator of transcription (STAT) signalling pathway, while overexpression of HERC6 led to the opposite results. In addition, AG490, a JAK/STAT pathway inhibitor, reversed the promoting effect of HERC6 overexpression on PBMC apoptosis and inflammation. In conclusion, the level of HERC6 in PBMCs in patients with SLE was upregulated. Overexpression of HERC6 promoted PBMC apoptosis and inflammatory response, which was involved in the JAK/STAT pathway.